Menyembuhkan Pikiran dengan Iman Analisis Prosedur Psikoterapi Islam untuk Kecemasan dan Stres: Tinjauan Literature - Adhelia Husnainy Zaen; Khairunnas Rajab (ALSYS, 2026)
Although Islamic psychotherapy has received attention in various previous studies, research that specifically discusses the structured procedures and clinical mechanisms of Islamic psychotherapy techniques for treating anxiety and stress in Muslim populations remains limited. This study aims to analyze and evaluate the main procedures of Islamic psychotherapy in treating anxiety and stress through a systematic literature review approach. This study used a qualitative method with a systematic literature review (SLR) design guided by PRISMA principles, involving 46 primary sources selected from the Google Scholar, PubMed, PsycINFO, and GARUDA databases and published between 1988 and 2022. Data were collected through document analysis and evaluated using thematic analysis techniques. The results showed that Islamic psychotherapy includes six structured main procedures, namely dhikr therapy as emotional regulation, shalat as transcendental meditation, tilawah and tadabbur of the Al-Qur’an as cognitive restructuring, fasting as nafs training, tawakkal as acceptance therapy, and ruqyah syar’iyyah as a spiritual intervention. These findings contribute to the development of the biopsychosociospiritual model of mental health and expand understanding of religion-based therapeutic interventions. The conclusion of this study confirms that Islamic psychotherapy, through the holistic integration of spiritual and psychological dimensions, plays an important role in reducing symptoms of anxiety and stress in Muslim clients. The implications of this study include theoretical contributions to the literature on Islamic psychology and practical recommendations for developing a more structured and standardized Islamic psychotherapy curriculum.